Participatory fecal collection on wild sumatran elephants' dungs in South Sumatra: The significant role of community involvement - Pratiwi, Dian Neli; P. Haryanto, Sugeng; Yanti, Yulianti; Arum, Setiawan; Samsul , Bakri; Winda, Indriyanti; Elly Lestari, Rustiati (BIOVALENTIA: Biological Research Journal, 2024)
Sumatran elephant Elephas maximus sumatranus is a critically endangered species under pressure of habitat fragmentation and human-elephant conflict (HEC) such as in one plantation and/or settlement area next to its natural habitat, Simpang Tiga Abadi, Selapan, South Sumatera.  Due to HEC, local people may experience economic loss and human casualty. Simpang Tiga Abadi is avillage, especially 5 sub-settlements directly close to the production forest area of PT. Bumi Khatulistiwa Mandiri, which is the natural habitat of sumatran elephants. The communities collaborated and company were formed an elephant watch group to monitor and deter sumatran elephants from entering plantation areas and settlements. On the other side, sumatran elephants entering the plantation may give some conservation support as indirect conflict mitigation approaches.   A non-invasive sampling can be done by gathering information on its fecal based genetic diversity and may become one of supporting sumatran elephant conservation efforts.   Under the Center for Applied Science Studies, Sriwijaya University project: "Genetic analysis of the sumatran elephant sub-population in its  habitat pocket in Sugihan- Simpang Heran, South Sumatra", Tropical Forest Conservation Action (TFCA) cycle VIII project, the significant role of local community affected by HEC on gathering information and fecal samples of sumatran elephant entering the PT.   Bumi Khatulistiwa Mandiri plantation was conducted.   Sumatran elephants’ fecal sampling involved the local communities affected by HEC. Its aim is to value the significance of local people’s involvement in finding and collecting dung left by wild sumatran elephants during entering both plantation areas. Data on areas were recorded, and its dung samples were collected for molecular analysis.  Collecting information and mapping the entry points of sumatran elephants were done supported by the Simpang Tiga Abadi community, consisting of sumatran elephant’s entry points, dung presence, individual numbers, and group activities, as well as the damage. Eighteen fecal samples of 5 entry points were collected in 5 days. By doing the assistance, the local communities learnt the benefits and important value of sumatran elephant and its dung.   This research is the first local communities’ indirect step in efforts to conserve sumatran elephants in Simpang Tiga Abadi Village, Selapan, South Sumatra.